2015
DOI: 10.21608/jppp.2015.74529
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF TWO PLANT EXTRACTS AND FOUR AROMATIC OILS ON Tuta absoluta POPULATION AND PRODUCTIVITY OF TOMATO CULTIVAR GOLD STONE

Abstract: Plants extracts and essential oils were used in pest management in different crops against various pests. Under field conditions, we examined the effect of two plant extracts and four essential aromatic oils on the response of tomato hybrid cultivar Gold Stone to Tuta absoluta infestation. Also, their effects on some growth characteristics of tomato plants as well as their total phenolic compounds and total flavonoids contents were explored in the two successive summer seasons of 2011 and 2012. The treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
(23 reference statements)
2
17
0
Order By: Relevance
“…Although induced resistance may not be entirely dedicated to these few findings, current findings hold enough information to establish grounds for future studies. Natural compounds have been shown to act as plant growth promoter, inducer, or elicitor for defense systems [85][86][87][88][89]. The effect, however, might depend on the plant and the stress implicated; therefore, the underlying molecular basis seems to be complicated.…”
Section: Biostimulation Of Defense System Leads To Induced Resistancementioning
confidence: 99%
“…Although induced resistance may not be entirely dedicated to these few findings, current findings hold enough information to establish grounds for future studies. Natural compounds have been shown to act as plant growth promoter, inducer, or elicitor for defense systems [85][86][87][88][89]. The effect, however, might depend on the plant and the stress implicated; therefore, the underlying molecular basis seems to be complicated.…”
Section: Biostimulation Of Defense System Leads To Induced Resistancementioning
confidence: 99%
“…This result may be regarded to garlic contains of enzymes, proteins, B vitamins, minerals, maillard reaction products and flavonoids which are non sulphur-containing compounds. Furthermore, a phytoalexin (allixin) which, is very important in the biological activities in the plant (Synge, 1971 andPandya et al, 2011).These results are in line with Morsy el al., (2009), Hussein et al, (2014. Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Morsy et al, (2009) stated that garlic extracts significantly improved all growth characteristics of cucumber plant and they found that garlic extract can be used to alleviate biotic and abiotic stresses. Hussein et al, (2014) reported that garlic extract significantly increased the yield of tomato in the first season and they also found that garlic extract gave the highest values of total phenolic compounds (TPCs) and total flavonoids (TFs) in treated tomato leaves. On soybean (Glycine max L.) plant, Mohamed and AkJadious (2014) decided that foliar spray with two concentrations of garlic extract (400 and 600 ppm) enhanced shoot and root length, leaf area, fresh and dry weight of shoots and roots and photosynthetic pigments i.e; chl a, chl b, carotenoids and total pigments.…”
Section: Introductionmentioning
confidence: 98%
“…Results obtained by Hussein et al [37] indicated that controlling T. absoluta by essential oil significantly affected fresh weight, shape index, total soluble solids, thickness of pericarp, pH and ascorbic acid. Interestingly, the tested plant extracts and essential oils affected the percentage of dry weight of fruits and vegetative growth of tomato plants significantly.…”
Section: Discussionmentioning
confidence: 98%
“…In this study garlic had moderate effectiveness on the pest. However, Hussein et al [37] showed a high reduction of T. absoluta population after tomato plants were treated with garlic extract. The moderate reduction of T. absoluta during this study was due to the extraction method that affects the presence of some volatile oil that confers to garlic its biological properties.…”
Section: Discussionmentioning
confidence: 99%